Acute Traumatic Spinal Cord Injury: Implementation of a Multidisciplinary Care Pathway. Issue 4 (July 2022) - Portelli Tremont, Jaclyn N.; Cook, Nicole; Murray, Laura Helen; Udekwu, Pascal Osi; Motameni, Amirreza T.
Abstract : BACKGROUND: Management of acute traumatic spinal cord injuries is complex, and patients are at risk for severe complications while inpatient. Performance review revealed opportunities for improvement in the care of patients with acute traumatic spinal cord injury at our institution. OBJECTIVE: To compare mortality, failure-to-rescue, and health care utilization of patients with acute traumatic spinal cord injury after implementation of a revised multidisciplinary care pathway. METHODS: Using a pre- and post-between-subjects study design, a retrospective cross-sectional analysis of consecutive patients admitted to our Level I trauma center with acute traumatic spinal cord injury was performed. An updated care pathway for all patients who presented with acute traumatic spinal cord injury was implemented in July 2020. This pathway includes a revised order set in the electronic medical record, distribution of a "best practice" guide to inpatient providers, a formal twice-daily respiratory evaluation, and weekly clinical nurse specialist-led patient rounds. RESULTS: One hundred and eight patients were included in analysis (prepathway: n = 52, postpathway: n = 56). Total mean hospital length of stay was 15.2 (14.0) and 21.5 (24.8) days for the pre- and postpathway groups. Eleven patients (21%) compared with six patients (11%) died, and failure-to-rescue occurred in six patients (60%) compared with zero patient in the pre- and postpathway groups, respectively. In addition, 10 (20%) postpathway patients were discharged to home compared with one (2%) in the prepathway group. DISCUSSION: Following implementation of the updated acute traumatic spinal cord injury pathway, overall inpatient mortality decreased, and fewer patients died after experiencing a complication. Results highlight the need for continued review of care practices and multidisciplinary review in quality improvement initiatives.